Oxidation behavior of Zr-Y alloyed Mo-Si-B based alloys. (April 2020) - Yang, Tao; Guo, Xiping
Abstract: Three Mo-Si-B based alloys (Mo-12Si-10B, Mo-12Si-10B-1Zr and Mo-12Si-10B-1Zr-0.3Y (at.%)) were fabricated to study the effects of Zr and especially further addition of Y on the oxidation behaviors of alloys at 1250 °C. Mo-12Si-10B alloy shows good oxidation resistance due to the formation of a protective SiO2 layer. However, as the result of the phase transformation of ZrO2, triggering the breaking up of the protective SiO2 layer, the addition of 1 at.% Zr (Mo-12Si-10B-1Zr alloy) leads to the catastrophic oxidation behavior. Further addition of 0.3 at.% Y (Mo-12Si-10B-1Zr-0.3Y alloy) eliminates this detrimental effect of Zr alloying by promoting the formation of monomorphic ZrSiO4 instead of polymorphic ZrO2 during oxidation. Besides, at the later oxidation stage (≥20 h), a continuous and compact Y2 Si2 O7 layer forms on the scale surface, further improving the oxidation resistance. Highlights: 1 at.% Zr addition to Mo-12Si-10B leads to catastrophic oxidation at 1250 °C. Further Y addition to Zr-containing alloy eliminates its catastrophic oxidation. Autogenous Y2 Si2 O7 layer further improves the oxidation resistance.